Joint Excitation and Reactive Power Control in Thermal Power Plant - Dragosavac, Jasna D; Janda, Žarko; Gajić, Tomislav; Dobričić, Sava; Pavlović, Jelena; Arnautović, Dušan (Proceedings, Electrical engineering institute "Nikola Tesla", 2013)
The coordinated voltage and reactive power controller, designed for the thermal power plant, is presented in the paper. A brief explanation of the need for such device is given and justification for commissioning of such equipment is outlined. After short description of the theoretical background of the proposed control design, the achieved features of the commissioned equipment are fully given. Achieved performances are illustrated by recorded reactive power and bus voltage responses after commissioning of the described equipment into the largest thermal power plant in Serbia. As it can be seen in presented records, all design targets are met.